Talking about God and Talking about Creation : Avicenna's and Thomas Aquinas' positions - Acar, Rahim, (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
Comparing Avicenna's and Thomas Aquinas' positions regarding human knowledge, this volumes talks about God and the nature of the creative action and the beginning of the universe. The overall argument of the book is that their conception of theological language plays an important role in shaping their positions concerning the creation of the universe. In the first part, their conception of the theological language and divine formal features are explored and how their positions regarding theological language differ from each other is discussed. The second part includes a comparison of their conceptions of the nature of the divine creative action-which provides a good example showing how their conceptions of theological language affect the way they talk about creation-and their arguments concerning the beginning of the universe.